MLVA as a Tool for Public Health Surveillance of Human Salmonella Typhimurium: Prospective Study in Belgium and Evaluation of MLVA Loci Stability - Wuyts, Véronique (Public Library of Science, 2013)
Surveillance of Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) is generally considered to benefit from molecular techniques like multiple-locus variable-number of tandem repeats analysis (MLVA), which allow earlier detection and confinement of outbreaks. Here, a surveillance study, including phage typing, antimicrobial susceptibility testing and the in Europe most commonly used 5-loci MLVA on 1,420 S. Typhimurium isolates collected between 2010 and 2012 in Belgium, was used to evaluate the added value of MLVA for public health surveillance. Phage types DT193, DT195, DT120, DT104, DT12 and U302 dominate the Belgian S. Typhimurium population. A combined resistance to ampicillin, streptomycin, sulphonamides and tetracycline (ASSuT) with or without additional resistances was observed for 42.5% of the isolates. 414 different MLVA profiles were detected, of which 14 frequent profiles included 44.4% of the S. Typhimurium population. During a serial passage experiment on selected isolates to investigate the in vitro stability of the 5 MLVA loci, variations over time were observed for loci STTR6, STTR10, STTR5 and STTR9. This study demonstrates that MLVA improves public health surveillance of S. Typhimurium. However, the 5-loci MLVA should be complemented with other subtyping methods for investigation of possible outbreaks with frequent MLVA profiles. Also, variability in these MLVA loci should be taken into account when investigating extended outbreaks and studying dynamics over longer periods.